Sistem Informasi Pengelolaan Persediaan Barang di BPJS Ketenaga Kerjaan Cabang Langsa - Sakdiani Lubis; Munawir (E-Jurnal Universitas Samudra, 2021)
The inventory management information system at BJPS Ketenagakerjaan Cabang Langsa is currently still being done manually, such as the data collection process in the warehouse. With a large number of items and not fixed, the process of collecting these items is very time consuming. So we need an information system for managing inventory of goods at BPJS Ketenagakerjaan Cabang Langsa. The system to be created is a Web-based system using Xampp as the server. The results of the creation of an inventory management information system, namely an inventory management information system have been successfully designed and created to assist the goods data collection process is carried out to determine the number of incoming goods, outgoing goods, and the remaining goods in a computerized warehouse using the system Web Based Inventory Management Information.